No evidence of early life resource pulse effects on age‐specific variation in survival, reproduction and body mass of female Siberian flying squirrels - Le Coeur, C.; Berger, V.; Lummaa, V.; Wistbacka, R.; Selonen, V. (Wiley, 2025)
1. Understanding the diversity and causes of senescence patterns in the wild remains a challenging task, in particular among fast-living species for which senescence patterns have been poorly studied. Early life environmental conditions can shape senescence by influencing trade-offs between early and late life performance (disposable soma theory) or individual fitness through lifelong positive effects (silver spoon effects).
2. Using a 23-year-long monitoring dataset of two populations of Siberian flying squirrels (Pteromys volans L.) in western Finland, we analysed the occurrence, onset and rate of senescence in female survival, body mass and reproductive performance. We also examined how early life pulsed resources (tree masting during the year of birth) influence age-specific variations in these traits.
3. Our results indicate that survival senescence occurs after sexual maturity from 3 years of age. Females experiencing high resource availability at birth tended to survive better, but the age-specific trend was not affected by early life resource conditions. Maternal body mass declined slightly with age, starting at 4 years, regardless of early resource conditions. Similarly, among reproductive traits, we showed late-onset senescence in both litter size and annual reproductive probability, with no evidence supporting an effect of early life resources on these trends. We found no decline in juvenile body mass or in the juvenile size-number trade-off with maternal age.
4. Our findings suggest that pulsed resources experienced at birth have a limited long-lasting impact on the life-history traits of this fast-living rodent, with no significant effect on senescence patterns.